Production of hydrogen by photoreforming of formaldehyde containing wastewater over CdO–CuO@exfoliated g–C3N4 nanoheterojunction - Thurga Devi, Munusamy (2022)
Today, population growth and development of industrializations creates huge dilemma by virtue of increasing global energy demand and environmental issues. To overcome the current challenges of fossil fuel depletion and ever–growing water pollution, intensive efforts have been taken towards exploring sustainable pathway to tackle the present problems. In this context, photocatalysis holds great promise as it harvests the widely available renewable source, solar energy to produce hydrogen. Accordingly, photocatalytic reforming or photoreforming of petrochemical wastewaters offers a sustainable routes for dual benefits of green energy production and wastewater remediation. The current research was intended to synthesize highly promising polymeric–based photocatalyst, graphitic carbon nitride (g–C3N4) as the support and further tuned by exfoliating the material and doped with metal oxides such as CdO and CuO. Subsequently, a novel CdO–CuO@exfoliated nanoheterojunction was constructed through a facile wet impregnation technique. From XRD results, the blue–shifting of the bulk g–C3N4 (27.90°) to lower peak of exfoliated g–C3N4 (27.15°), creating more spaces between the inter–planar layers thereby revealing successful distortion of the triazine planar and formation of nanosheets. Moreover, BET results showed large improvement of the specific surface area of exfoliated g–C3N4 (104.4 m2/g) and CdO–CuO@exfoliated g–C3N4 (388.4 m2/g) by 3 and 11 times respectively compared to bulk g–C3N4 (34.5 m2/g). Subsequently, the as–synthesized photocatalysts were tested for the photoreforming activity of hydrogen production in aqueous formaldehyde medium and irradiated under LED light. As an outcome, the activity trend for the hydrogen was in an order of bulk g–C3N4 < exfoliated g–C3N4 < CdO@exfoliated g–C3N4 < CuO@exfoliated g–C3N4< CdO–CuO@exfoliated g–C3N4. An excellent activity of the nanoheterojunction was highly contributed by large surface area caused more active sites available for the redox reactions. Moreover, the tremendous reduction of peak intensity in PL analysis greatly hinders the recombination rate of electron–hole pairs, thereby promoting facile charge separations and migrations, fostering the hydrogen production. Thereafter, CdO–CuO@exfoliated g–C3N4 was further examined to optimize the parameters and study the correlation between different factors. Based on the ANOVA, the model was well–fitted with F–value and p–value of 54.97 and <0.0001 (less than 0.05) respectively. Besides, the interactions between the diverse parameters were investigated and demonstrated via the contour and three–dimensional plots. The maximum hydrogen produced was 9025 μmol/g for following conditions: reaction time of 8 h, catalyst dosage of 0.73 g/L, initial FA–concentration of 573 ppm and light intensity of 152 W/m2. The developed n–n–p heterojunction catalyst demonstrated higher hydrogen yield compared to the existing catalytic systems. By referring to Mott–Schottky analysis and proposed charge transfer mechanism, the formulation of unique band structure of n–n–p CdO–CuO@exfoliated g–C3N4 nanoheterojunction fulfilled the photoreforming reduction and oxidation potentials, subsequently enhancing the charge separation and migrations, thus leading to an efficient hydrogen production performance. From the LSV results and Tafel slopes, CdO–CuO@exfoliated g–C3N4 exhibits best HER activity with smallest Tafel slope value of 53 mV/dec among all the prepared electrodes. Apart from that, an autocatalytic kinetic model was proposed and exhibits excellent fitting for the photoreforming reactions as evidenced from the plot of experimental and theoretical rates as well as high R2 values for all the initial formaldehyde concentrations. Hence, the present research provides meaningful insights for the development of novel photocatalyst by combining different vi junctions and the applications for simultaneous generation of green energy as well as valorization of wastewaters.